Cytology and Human Papillomavirus Testing 6 to 12 Months after ASCUS or LSIL Cytology in Organized Screening To Predict High-Grade Cervical Neoplasia between Screening Rounds - Tropé, Ameli (American Society for Microbiology, 2012)
We carried out a prospective study comparing the performance of human papillomavirus (HPV) E6/E7 mRNA (PreTect HPV-Proofer; NorChip, Klokkarstua, Norway) and DNA (Amplicor HPV test; Roche Diagnostics, Basel, Switzerland) triage testing of women 6 to 12 months after atypical-squamous-cells-of-undetermined-significance (ASCUS) or low-grade-squamous-intraepithelial-lesion (LSIL) cytology in organized screening to predict high-grade cervical intraepithelial neoplasia of grade 2 or worse (CIN2+) between screening rounds. Between January 2005 and April 2008, 692 study women with screening-detected ASCUS/LSIL cytology 6 to 12 months earlier returned for HPV mRNA and DNA testing and repeat cytology. The median follow-up time was 3 years, using existing health care facilities. Follow-up test results were available for 625 women. Of the 145 CIN2+ cases detected during the study period, 95 (65.5%) were HPV mRNA positive 6 to 12 months after screening-detected ASCUS/LSIL, 44 (30.4%) were HPV mRNA negative, and 6 (4.1%) were invalid. The corresponding HPV DNA results were 139 (95.9%), 5 (3.4%), and 1 (0.7%), respectively. The cumulative incidences of CIN2+ 3 years after a negative HPV mRNA and DNA test were 10.3% (95% confidence interval [CI], 7.2 to 13.3%) and 1.8% (95% CI, 0.0 to 3.6%), respectively. The cumulative incidences of CIN2+ 3 years after positive HPV mRNA and DNA tests were 52.8% (95% CI, 40.1 to 60.1%) and 41.3% (95% CI, 35.5 to 46.6%), respectively. In conclusion, both positive HPV mRNA and DNA test results have a high enough long-term prediction of CIN2+ risk to consider referral to colposcopy as good practice when performed in delayed triage of women with ASCUS/LSIL cytology. In addition, the low CIN2+ risk among women with a negative Amplicor HPV test in our study confirms its safe use in a clinical setting.